Karakter Perempuan Jawa Dalam Leksikon Jawa - M Suryadi (Program Studi Sastra Indonesia, Fakultas Ilmu Budaya, Universitas Diponegoro, 2018)
This study aims to identify the Java lexicon. The Javanese lexicon which has a relation to the character of Javanese women. The Java Lexicon which is the focus of the study is vocabulary based on the meaning of the components of the character: behavior, habits and character. Location of research in the northern coast of Central Java. Data collection methods are observation, interview (structured interview and in-depth interview), and focus grop discussion (FGD). The analytical method is the equivalent method. Using three analytical techniques: reconstruction, correlation, and context matching. The theoretical basis used is adhesion: the word-concept-referent and Sapir-Worf hypothesis. Research findings are 1) Javanese female characters are reflected in the lexicon; 2) Lexicon of Javanese female characters can be traced internally (word structure) and external (context and philosophy); 3) internal studies are analyzed diachronically and synchronously; 4) External studies are analyzed involving the components of context and cultural order that have philosophical values (micro and macro); 5) The order of word-concept-referent is a formula for reconstructing forms and meanings.